Nano cellulose-chitosan bio-based antibacterial agent and non-woven material based on nano cellulose-chitosan bio-based antibacterial agent
By preparing nanocellulose-chitosan bio-based antibacterial agents, the antibacterial and mechanical properties of PLA-based nonwoven materials are improved by using multi-dimensional synergy, the problems of weak material binding force and low antibacterial efficiency are solved, and high-efficiency antibacterial and excellent mechanical properties are achieved, which are suitable for a variety of high-value-added fields.
Patent Information
- Application Number
- CN202510336498.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In meltblown processing, existing PLA-based nonwoven materials have weak bonding force between fiber layers and insufficient material peel strength due to low PLA melt strength. At the same time, the lack of functional modification leads to low antibacterial efficiency, which seriously restricts its application in high-value-added fields such as medical dressings and food packaging.
By preparing nanocellulose-chitosan bio-based antibacterial agents, the multi-dimensional synergy of quaternary ammonium salts, chitosan and nanocellulose are used to form a dynamic antibacterial process of "adsorption enrichment-active release-membrane destruction", which improves the antibacterial performance of the material, and improves the mechanical and thermal properties of the material through melt blending and melt spinning technology.
It has achieved efficient antibacterial, improved the mechanical strength, toughness and thermal performance of materials, and broke through the mutually exclusive bottleneck of "functional-mechanical" performance. It is suitable for home textiles, packaging materials and biomedical fields.
Smart Images

Figure CN119842082A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer melt-blown nonwoven materials, in particular to a nano-cellulose-chitosan bio-based antibacterial agent and a nonwoven material based thereon. Background Art
[0002] As a new type of fiber aggregate, nonwoven materials have deeply penetrated into aerospace, environmental engineering, modern agriculture, medical care and daily life due to their unique pore structure and processing convenience. Driven by the global sustainable strategy, the ecological accumulation problem caused by the lack of biodegradability of traditional petroleum-based nonwoven materials has become increasingly prominent. This severe situation has prompted biodegradable nonwoven materials to become the core direction of global industrial transformation and upgrading. Polylactic acid (PLA), as a typical bio-based polyester material, is regarded as an ideal candidate to replace traditional plastics due to its crystallization adjustability, moderate mechanical properties and complete degradation characteristics of 6-12 months under composting conditions. However, the industrial application of PLA-based nonwoven materials still faces three technical barriers: (1) the weakening of the inter-fiber bonding force due to the low melt strength of PLA during the melt-blown process, resulting in insufficient material peeling strength; (2) intrinsic brittleness and impact resistance defects; (3) the low antibacterial efficiency caused by the lack of functional modification (the antibacterial rate against Escherichia coli is <50%), which seriously restricts its application in high value-added fields such as medical dressings and food packaging.
[0003] In view of the defects in mechanical properties, the existing technologies mostly adopt the strategy of blending modification: Patent CN116219636B (a method for preparing a high-strength and high-toughness degradable melt-blown nonwoven material) innovatively introduces polybutylene succinate (PBS) and PLA to construct an island structure, and improves the toughness through the plastic deformation of the PBS phase, so that the elongation at break of the composite material is increased to 4.5%-40.5%. However, the interface compatibility between PBS and PLA in this method is poor, which easily causes phase separation and reduces the service stability of the material. In terms of functional modification, surface grafting and bulk blending constitute two major technical routes. Patent CN115624646B (an antibacterial liquid-absorbing nonwoven material for sanitary products) adopts a three-step method of plasma activation-dopamine bionic modification-antibacterial agent impregnation to load quaternized carboxymethyl chitosan on the surface of the material, which has a good antibacterial effect on Escherichia coli. However, the surface modification technology has the inherent defect of insufficient antibacterial persistence. The melt blending method used in patent CN117758444A (a long-lasting antibacterial meltblown cloth and its preparation method) achieves an antibacterial effect of more than 99% on Escherichia coli and Staphylococcus aureus through the synergistic effect of chitosan quaternary ammonium zinc complex and carbon nanotube-based antibacterial agent, but the stress concentration phenomenon caused by nanoparticle agglomeration reduces the elongation at break of the material, forming a dilemma of "functional-mechanical" performance. Patent CN114957940B (a method for preparing polylactic acid meltblown material and its application) melt-blends polylactic acid, toughening agent and other additives modified by quaternary ammonium cellulose nanocrystals to obtain polylactic acid meltblown material, which can increase its mechanical properties and antibacterial properties while ensuring the degradation performance of the meltblown cloth. However, the patent does not introduce the improvement of the toughness of polylactic acid meltblown cloth by quaternary ammonium cellulose nanocrystals. Therefore, how to improve the mechanical strength, toughness index and antibacterial durability of PLA-based nonwoven materials while maintaining their biodegradability through material design and process innovation, and break through the mutually exclusive bottleneck of "functional-mechanical" performance, has become a common challenge faced by the current technology system. This has become a key scientific issue in promoting the leap of degradable nonwoven materials into high-end application fields. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a nanocellulose-chitosan bio-based antibacterial agent and a method for preparing a long-lasting antibacterial biodegradable non-woven material based thereon, so as to make the obtained biodegradable non-woven material have high antibacterial properties, high strength and toughness, as well as excellent heat resistance and processing properties, and can be applied to home textiles, packaging materials, biomedicine and other fields.
[0005] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme: The present invention first provides a method for preparing a nanocellulose-chitosan bio-based antibacterial agent. Based on the amino characteristics on the chitosan molecular chain, the functional modification of quaternary ammonium salt is first achieved through an epoxy ring-opening reaction. The specific steps are: a nucleophilic substitution reaction is caused between the free amino groups on the surface of chitosan and the epoxy groups of 2,3-epoxypropyltrimethylammonium chloride, and the quaternary ammonium salt groups are covalently grafted to the chitosan main chain through intermolecular dehydration to obtain a quaternized chitosan intermediate. Subsequently, the nanocellulose is subjected to an oxidative modification treatment: a selective oxidant (such as sodium periodate) is used to directionally oxidize the surface hydroxyl groups of the nanocellulose into active aldehyde groups to prepare oxidized nanocellulose. On this basis, through an aldehyde-amine condensation reaction, the aldehyde groups of the oxidized nanocellulose and the amino groups of the quaternized chitosan form a stable Schiff base bond to construct a three-dimensional network structure composite antibacterial agent. The composite system achieves high antibacterial efficiency through a triple synergistic mechanism: (1) quaternary ammonium salt cations destroy the electrical potential balance of bacterial cell membranes through electrostatic action, resulting in abnormal membrane permeability and leakage of intracellular substances; (2) chitosan molecules block microbial metabolic pathways through metal ion chelation, enhancing the antibacterial persistence of quaternary ammonium salts; (3) nanocellulose achieves bacterial enrichment effect by virtue of its high specific surface area, and its nano-network structure can physically block microbial migration and colonization. The three components work together in multiple dimensions of "chemistry-physics-structure" to form a dynamic antibacterial process of "adsorption enrichment-active release-membrane destruction", producing a significant synergistic effect (1+1+1>3 effect).
[0006] Furthermore, the method for preparing the nanocellulose-chitosan bio-based antibacterial agent of the present invention specifically comprises the following steps: (1) Preparation of quaternary ammonium chitosan: First, disperse chitosan in isopropanol and stir at 65-90°C for 1-2 hours to obtain a chitosan solution; then add an aqueous solution of 2,3-epoxypropyltrimethylammonium chloride and stir at the reaction temperature for 10-16 hours; after the reaction, filter and clean the obtained precipitate with isopropanol and ethanol in turn, dry and crush to obtain quaternary ammonium chitosan.
[0007] (2) Preparation of oxidized nanocellulose: Dissolve the selective oxidant in water, then add nanocellulose to mix to obtain a selective oxidant / nanocellulose mixed solution. Place the solution in a dark place and stir for 1-3 hours to form a gel solution. Then dilute it with water and filter it to obtain oxidized nanocellulose.
[0008] (3) Preparation of nanocellulose-chitosan bio-based antimicrobial agent: dissolve the quaternized chitosan obtained in step (1) in 1-3% by volume acetic acid solution, and stir for 2-4 hours to obtain a homogeneous mixed solution containing quaternized chitosan; then add the oxidized nanocellulose obtained in step (2) to the homogeneous mixed solution, stir at a constant temperature of 40-79°C for 1-3 hours, remove the acetic acid by rotary evaporation, dry and grind to obtain the nanocellulose-chitosan bio-based antimicrobial agent.
[0009] Preferably, in step (1), the concentration of chitosan in the chitosan solution is 0.01-0.05 g / mL; the concentration of 2,3-epoxypropyltrimethylammonium chloride in the aqueous solution of 2,3-epoxypropyltrimethylammonium chloride is 0.1-0.3 g / mL; and the mass ratio of chitosan to 2,3-epoxypropyltrimethylammonium chloride is 1:3-10.
[0010] Preferably, in step (2), the selective oxidant is sodium periodate, or a mixture of 2,2,6,6-tetramethylpiperidinyl oxide, sodium bromide and sodium hypochlorite in a mass ratio of 0.1-0.2:1-2:20-30.
[0011] Preferably, in the selective oxidant / nanocellulose mixed solution, the concentration of the selective oxidant is 0.02-0.04 g / mL, and the mass ratio of the selective oxidant to the nanocellulose is 2-4:1.
[0012] Preferably, in step (2), the nanocellulose is at least one of cellulose nanofibers, cellulose nanowhiskers, cellulose nanocrystals and bacterial nanocellulose.
[0013] Preferably, in step (3), the ratio of the quaternized chitosan, acetic acid solution and oxidized nanocellulose is 1 g:70-100 mL:1 g.
[0014] The present invention further provides a method for preparing a long-lasting antibacterial biodegradable nonwoven material, which comprises premixing, melt blending and melt spinning the above-mentioned nanocellulose-chitosan bio-based antibacterial agent with polylactic acid, tough biodegradable material (toughening agent), epoxy chain extender and processing aid to prepare the biodegradable nonwoven material. The innovation of the preparation method is reflected in: (1) after the epoxy group of the chain extender is ring-opened, it forms a covalent bond with the active groups such as hydroxyl and carboxyl groups on the surface of each component, which significantly improves the interfacial compatibility between the bio-based antibacterial agent, polylactic acid and tough biodegradable material; (2) the antibacterial agent has the dual functions of a functional modifier and a nucleating agent, which can not only improve the antibacterial performance of the material, but also promote the crystallization of polylactic acid through heterogeneous nucleation, thereby improving the mechanical properties and thermal properties of the material; (3) the synergistic effect of the toughening agent and the chain extender improves the toughness of the material, and the high toughness makes the biodegradable nonwoven material soft and comfortable, while maintaining a biodegradation rate of more than 95%.
[0015] Furthermore, the method for preparing the biodegradable nonwoven material of the present invention specifically comprises the following steps: The nanocellulose-chitosan bio-based antibacterial agent is evenly mixed with polylactic acid, tough biodegradable materials, epoxy chain extenders, lubricants and antioxidants in a mixer, and then extruded, granulated and dried through a twin-screw extruder, and then melt-blown in a melt-blown device to obtain a long-lasting antibacterial biodegradable non-woven material.
[0016] Preferably, the tough biodegradable material is at least one of polybutylene terephthalate-adipate (PBAT), polybutylene succinate (PBS), polybutylene succinate-adipate (PBSA) and polybutylene terephthalate-succinate (PBST); the lubricant is at least one of calcium stearate, magnesium stearate, zinc stearate, aluminum stearate, barium stearate and sodium stearate; and the antioxidant is at least one of hindered phenol antioxidants, hindered amine antioxidants, phosphite antioxidants and thioester antioxidants.
[0017] Preferably, the weight ratio of the nanocellulose-chitosan bio-based antibacterial agent, polylactic acid, tough biodegradable material, epoxy chain extender, lubricant and antioxidant is 0.5-5:40-60:40-80:0.5-2:0.1~1:0.1~1.
[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. The three components of nanocellulose, quaternary ammonium salt and chitosan in the nanocellulose-chitosan bio-based antibacterial agent of the present invention cooperate in multiple dimensions of "chemistry-physics-structure" to form a dynamic antibacterial process of "adsorption enrichment-activity release-membrane destruction", producing a significant synergistic effect (1+1+1>3 effect), thereby achieving high-efficiency antibacterial effect.
[0019] 2. The nanocellulose-chitosan bio-based antibacterial agent of the present invention has the dual role of a functional modifier and a nucleating agent, which can not only improve the antibacterial properties of the material, but also promote the crystallization of polylactic acid through heterogeneous nucleation, and synergistically improve the interface compatibility, mechanical properties and thermal properties of the material with the chain extender.
[0020] 3. The main body of the nanocellulose-chitosan bio-based antibacterial agent of the present invention adopts nanocellulose and chitosan which are abundant and renewable in nature, and the main body of the nonwoven material adopts biodegradable material, which has biocompatibility, conforms to the concept of green environmental protection, and is suitable for large-scale production.
[0021] 4. The long-lasting antibacterial and biodegradable nonwoven material prepared by the present invention has the advantages of high antibacterial property, high strength and toughness, good heat resistance and excellent processing performance, and is suitable for home furnishings, packaging materials, biomedicine and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Diagram of the synthesis mechanism of chitosan grafted cellulose nanocrystals.
[0023] Figure 2 The chemical composition characterization results of the nanocellulose-chitosan bio-based antibacterial agent prepared in Example 1 are as follows: Figure 2 (a) is the infrared spectrum, (b) is the XRD diagram, (c) is the X-ray photoelectron spectrum, and (d) is the N1s spectrum.
[0024] Figure 3 The mechanical properties test results of the nonwoven materials obtained in Examples 1-5 and Comparative Example 1 are shown in FIG. Figure 3 (a) is the stress-strain curve, (b) is the tensile strength and Young's modulus, and (c) is the elongation at break and tensile toughness.
[0025] Figure 4 For comparative example 1 (corresponding to Figure 4 (a), (a')), Examples 1 to 5 (corresponding to Figure 4 SEM images of the fracture morphology of the nonwoven materials obtained after tensile testing (b), (b') to (f), (f').
[0026] Figure 5(a), (b), and (c) are the TG, DTG, and DSC curves of the nonwoven materials obtained in Examples 1-5 and Comparative Example 1, respectively.
[0027] Figure 6 The antibacterial effect diagram of Escherichia coli after being cultured on the nonwoven material discs of Comparative Example 1 and Example 4 for 0 h, 0.5 h, 1 h, 2 h, 4 h and 6 h respectively.
[0028] Figure 7 This is a comparison chart of the antibacterial rates of Escherichia coli after being cultured on the nonwoven material discs of Comparative Example 1 and Example 4.
[0029] Figure 8 The processing performance test results of the nonwoven materials obtained in Examples 1-5 and Comparative Example 1 are shown in FIG. Figure 8 (a) is the storage modulus, (b) is the loss modulus, and (c) is the complex viscosity. DETAILED DESCRIPTION
[0030] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art may make some non-essential improvements and adjustments based on the above contents of the present invention, which still fall within the scope of protection of the present invention.
[0031] Example 1 This embodiment provides a method for preparing a nanocellulose-chitosan bio-based antibacterial agent and a long-acting antibacterial biodegradable nonwoven material, and the specific steps are as follows: (1) 3.0 g of chitosan was placed in a 250 mL round-bottom flask, and then 120 mL of isopropanol was added, and the mixture was stirred at 85°C for 1 h to obtain a chitosan solution; then a mixture of 10.0 g of 2,3-epoxypropyltrimethylammonium chloride and 60 mL of water was added, and the reaction was continued in a magnetic stirrer at 85°C for 12 h; after the reaction was completed, the precipitate was taken out and filtered, and the precipitate was washed with isopropanol solution during the filtration process. After the filtration was completed, the precipitate was added to 50 mL of anhydrous ethanol under stirring, and then the precipitate was filtered out and stirred with ethanol for 2 h, and then filtered again to obtain a precipitate. The precipitate was placed in a 70°C oven and dried for 24 h, and crushed to obtain quaternized chitosan.
[0032] (2) Dissolve 6 g of sodium periodate in water at a concentration of 0.04 g / mL, add 3.0 g of cellulose nanocrystals and mix. Place in a dark place and stir for 2 h to form a gel solution. Then dilute with a large amount of water and filter to obtain oxidized cellulose nanocrystals.
[0033] (3) Weigh 1.0 g of quaternized chitosan and add it to 80 mL of 2% by volume acetic acid solution. Stir for 3 h to obtain a homogeneous solution containing quaternized chitosan. Add 1.0 g of oxidized cellulose nanocrystals to the homogeneous solution and stir at 50 °C for 1 h. After removing acetic acid by rotary evaporation, dry in a vacuum oven at 100 °C for 24 h and grind to obtain a nanocellulose-chitosan bio-based antibacterial agent.
[0034] (4) Nanocellulose-chitosan bio-based antibacterial agent, polylactic acid (2002D, Nature Works, USA), PBAT (801T, Blue Mountain Tunhe), chain extender (ADR4400, BASF, Germany), lubricant (calcium stearate, Kao, Japan), antioxidant 1010 and antioxidant 168 were weighed according to the following weight parts: 0.5 parts, 40 parts, 60 parts, 1 part, 0.9 parts, 0.5 parts and 0.5 parts, and mixed evenly in a high-speed mixer, and then extruded, granulated and dried by a twin-screw extruder, and then melt-blown and spun in a melt-blown equipment to obtain a long-lasting antibacterial and biodegradable melt-blown nonwoven material.
[0035] Example 2 In this example, the nanocellulose-chitosan bio-based antibacterial agent and the long-acting antibacterial biodegradable nonwoven material are prepared by the same method as in Example 1, except that the weight portion of the nanocellulose-chitosan bio-based antibacterial agent in step (4) is 1.0 part.
[0036] Example 3 In this example, the nanocellulose-chitosan bio-based antibacterial agent and the long-acting antibacterial biodegradable nonwoven material are prepared by the same method as in Example 1, except that the weight portion of the nanocellulose-chitosan bio-based antibacterial agent in step (4) is 1.5 parts.
[0037] Example 4 In this example, the nanocellulose-chitosan bio-based antibacterial agent and the long-acting antibacterial biodegradable nonwoven material are prepared by the same method as in Example 1, except that the weight portion of the nanocellulose-chitosan bio-based antibacterial agent in step (4) is 2.0 parts.
[0038] Example 5 In this embodiment, a nanocellulose-chitosan bio-based antibacterial agent and a long-lasting antibacterial biodegradable nonwoven material are prepared by the same method as in Example 1, except that: in step (2), the selective oxidant used in preparing oxidized cellulose nanocrystals is a 2,2,6,6-tetramethylpiperidinyl oxide / sodium hypochlorite / sodium bromide oxidation system, and the weight ratio of 2,2,6,6-tetramethylpiperidinyl oxide, sodium bromide and sodium hypochlorite is 0.1:1:25; in step (4), the weight portion of the nanocellulose-chitosan bio-based antibacterial agent is 2.5 parts.
[0039] Comparative Example 1 Polylactic acid (2002D, Nature Works, USA), PBAT (801T, Blue Mountain Tunhe), chain extender (ADR4400, BASF, Germany), lubricant (calcium stearate, Kao, Japan), antioxidant 1010 and antioxidant 168 were weighed according to the following weight parts: 40 parts, 60 parts, 1 part, 0.9 part, 0.5 part and 0.5 part, and mixed evenly in a high-speed mixer, and then extruded, granulated and dried by a twin-screw extruder, and then melt-blown and spun in a melt-blown equipment to obtain a biodegradable melt-blown nonwoven material.
[0040] The samples obtained from each embodiment and comparative example were subjected to the following performance tests: 1. Chemical composition test of nanocellulose-chitosan bio-based antimicrobial agent The nanocellulose-chitosan bio-based antibacterial agent prepared in Example 1 was dried and ground with potassium bromide powder, and then pressed into tablets after being uniformly mixed. The samples were tested using an FTIR-430 infrared spectrometer (FT-IR), and the spectral range was from 4000 cm -1 Up to 500 cm -1 , the results are as follows Figure 2 (a) is shown. Subsequently, the nanocellulose-chitosan bio-based antibacterial agent was pressed to a flat surface using a tablet press and then vacuum dried. The sample was measured using a Shimadzu XRD 7100 diffractometer (XRD). The scanning conditions were: using a voltage of 40 kV and Cu Kɑ rays, an operating current of 30 mA, a scanning range of 2θ=10~50°, and a scanning step of 1 deg / min, which can achieve high-precision measurements. The results are shown in Figure 2 Finally, the nanocellulose-chitosan bio-based antibacterial agent powder was analyzed using a Nexsa X-ray photoelectron spectrometer with Al Kɑ rays as the excitation source. The results are shown in Figure 2 (c) and Figure 2 (d) as shown.
[0041] from Figure 2 From the curve (1) in (a), we can see that 1599cm -1 It shows an obvious absorption peak, which represents the characteristic peak of NH bending vibration of amino group. Figure 2 In the curve (2) of (a), a ring-opening substitution reaction occurred between the amino groups on chitosan and the epoxy groups on the quaternary ammonium salt, resulting in the gradual disappearance of the absorption peak, indicating that 2,3-epoxypropyltrimethylammonium chloride was grafted onto N. Figure 2 Compared with the curve (1) in (a), Figure 2 (a) (2) curve at 1631cm -1and 1487cm -1 At , the curve shows a new characteristic peak, which indicates that the CH bending vibration peak of the methyl group in the quaternary ammonium salt is significantly enhanced, which can explain that the quaternary ammonium salt is successfully grafted onto chitosan. Figure 2 It can be seen from the curve (3) of (a) that at 3423 cm -1 The OH stretching vibration peak at 1050cm -1 The stretching vibration peak of -COC- at 1020 cm -1 The peak at represents the skeleton stretching vibration peak of CO. Figure 2 It can be seen from the curve (4) of (a) that the infrared spectrum of the nanocellulose-chitosan bio-based antibacterial agent retains the main characteristic peaks of cellulose nanocrystals at 868 cm -1 At , an obvious NH out-of-plane bending vibration peak appears. This is because the amino groups on the quaternized chitosan react with the aldehyde groups on the oxidized cellulose nanocrystals to form imines, and the C=N bond of the imine can be added by the amino group of another molecule to form a secondary amine structure called R1-NH-CH2-NH-R2. Therefore, it exists in the infrared spectrum of the nanocellulose-chitosan bio-based antibacterial agent in the form of a secondary amine absorption peak, and Figure 2 (a) Curve (4) at 3300 cm -1 ~3500 cm -1 In the range of 1631 cm -1 At the position of , the NH bending peak overlapping with the CH bending vibration peak can be found. This indicates that a graft copolymerization reaction has occurred between quaternized chitosan and oxidized cellulose nanocrystals.
[0042] Figure 2 In the chitosan and quaternized chitosan curves of (b), a strong characteristic peak is observed at 2θ of 20°, which is the characteristic peak of chitosan and represents the (110) crystal plane. The two diffraction peaks at 2θ of 10.8° and 25.9° are caused by the hydrogen bonding inside the chitosan. The diffraction peaks of quaternized chitosan at 2θ of 16.5° and 25.9° disappear. The results show that the quaternary ammonium salt groups react with the amino groups on the chitosan molecular chain to form a ring-opening reaction. The disordered arrangement of the chitosan molecules greatly weakens the effect of the hydrogen bonds and destroys the crystal structure, so the diffraction peaks disappear. Figure 2In the cellulose nanocrystal and nanocellulose-chitosan bio-based antimicrobial agent curve (b), the cellulose nanocrystal is a rod-shaped crystal with two characteristic diffraction peaks, 2θ of 20° and 34.7°. The diffraction peak of the grafted product nanocellulose-chitosan bio-based antimicrobial agent at 2θ=20° is weakened, and the diffraction peak at 2θ=34.7° disappears. This is because the amino group on the quaternized chitosan reacts with the aldehyde group on the cellulose nanocrystal to form a Schiff base reaction. When the original molecular chain is disrupted, the effect of the hydrogen bond will be weakened, and the crystal structure will also be affected, resulting in a decrease in crystallinity. This shows that the graft copolymerization reaction between the quaternized chitosan and the cellulose nanocrystal has been completed.
[0043] Figure 2 In (c), the quaternary ammonium chitosan collected carbon (57.96%), oxygen (35.27%), nitrogen (5.94%), and chlorine (0.81%) element absorption peaks, while the surface of the nanocellulose-chitosan bio-based antibacterial agent detected carbon (57.25%), oxygen (39.17%), nitrogen (3.16%), and chlorine (0.12%) element absorption peaks. The content of oxygen element increased, and the content of nitrogen and chlorine elements decreased. This is because the quaternary ammonium chitosan was grafted onto the cellulose nanocrystals, resulting in a large amount of -CO- and -C=O- on the cellulose nanocrystals. Further observation of the nitrogen spectrum of high-resolution XPS found that the absorption peaks of 402.5eV and 399.7eV were caused by -NH- and -CN- chemical bonds, respectively. Figure 2 In (d), the grafting of quaternized chitosan, because the entire Schiff base reaction involves -NH2 on the quaternized chitosan, -NH2 combines with -CHO to form a CN bond, so the NH bond in N1s will change. The quaternized chitosan before the Schiff base reaction shows NH bonds in the N1s spectrum. As the Schiff base cross-linking reaction occurs, the NH bonds gradually decrease, further indicating the process of -NH2 combining with -CHO to form a CN bond.
[0044] 2. Mechanical properties test of nonwoven materials The nonwoven materials prepared in each embodiment and comparative example were cut into pieces, and specimens and discs were made using a flat-plate vulcanizer. The temperature was set to 180°C, the pressure value was set to 10 MPa, preheated for 15 minutes and the holding time was set to 10 minutes. The mold filled with granules was placed between the upper and lower templates of the flat-plate vulcanizer, and the mold was closed while ensuring that the mold did not slip. After compression molding, the sample was taken out. The final prepared specimen had a length × width × height of 100 mm × 10 mm × 2 mm, and the diameter of the disc was about 25 mm. The specimens were numbered and placed for testing. The mechanical properties of the specimens were evaluated at a tensile rate of 10 mm / min using an XLW-500 tensile strength testing machine in accordance with ISO 527 specifications. The results are as follows: Figure 3 shown.
[0045] Depend on Figure 3 It can be seen that the tensile strength, elongation at break, Young's modulus and tensile toughness of the nonwoven material obtained in Comparative Example 1 are 5.79 MPa, 36.91%, 18.28 MPa and 1.02191 MJ / m respectively. 3 After adding the nanocellulose-chitosan bio-based antibacterial agent, the mechanical properties of the material are improved. For example, the tensile strength, elongation at break, Young's modulus and tensile toughness of the nonwoven material obtained in Example 4 are 9.13MPa, 73.72%, 24.63MPa and 3.26584MJ / m 3 Compared with Comparative Example 1, the tensile strength and elastic modulus of the nonwoven material obtained in Example 4 increased by 57.69% and 34.73%, respectively, and the elongation at break and tensile toughness increased by 99.73% and 219.6%, respectively. Figure 4 As shown: the sample surface of comparative example 1 is smooth, indicating brittle fracture; the sample of example 5 has obvious lumps and the surface of the local fracture area is rough; for the sample of example 4, the dimple surface along some of the pulled out cellulose nanocrystals (white spots) can be observed, and compared with example 5, the pulled out nanocellulose-chitosan bio-based antibacterial agent is better dispersed in the matrix. This is because the introduction of quaternized chitosan in the nanocellulose-chitosan bio-based antibacterial agent improves the dispersion of cellulose nanocrystals in the matrix, and the molecular entanglement and mechanical interlocking between cellulose nanocrystals and the matrix enhance the interface interaction between cellulose nanocrystals / matrix, thereby achieving effective transmission of stress from the matrix to the cellulose nanocrystals.
[0046] 3. Thermal performance test of nonwoven materials The nonwoven materials prepared in each embodiment and comparative example were dried in an oven at 60°C for 5 h. In a nitrogen-filled environment, the thermogravimetric analysis (TGA) of the samples between 25°C and 800°C was measured at a rate of 20°C / min using a Mettler Toledo TGA2 thermogravimetric analyzer under a nitrogen atmosphere. The thermal properties were tested using a DSC Q2000 analyzer (DSC).
[0047] The nonwoven materials prepared in each embodiment and comparative example were dried in an oven at 100°C, and 2-5 mg of the sample was placed in an alumina crucible for measurement. In order to ensure the accuracy of the test results, the test procedure was divided into two heating procedures: the first heating was intended to eliminate the thermal history, and the second heating was used to obtain the final data of this experiment. The specific operating procedure is: at a heating rate of 10°C / min, the temperature was gradually increased from 30°C to 180°C and maintained for five minutes, then decreased at a rate of 10°C / min, maintained for another five minutes, and finally increased to 180°C again. After the second heating experiment, nitrogen was used as the protective gas, and the relevant data were carefully recorded and analyzed. For relevant data, see Figure 5 and Table 1.
[0048] Depend on Figure 5 (a) and Figure 5 (b) It can be seen that the nanocellulose-chitosan bio-based antibacterial agent significantly increases the maximum thermal decomposition temperature of the first stage (320-380°C) of the material, but has no significant effect on the thermal decomposition temperature of the second stage (390-450°C). Figure 5 (c) and Table 1 show that the crystal content value of Comparative Example 1 is 0.8%, while the crystal content values of Examples 1 to 5 are between 1% and 2.7%. This shows that the nanocellulose-chitosan bio-based antibacterial agent can be used as an effective nucleating agent, greatly improving the non-isothermal crystallization rate of the material, thereby improving the thermal stability of the material.
[0049] Table 1
[0050] 4. Antibacterial performance test of nonwoven materials The antibacterial test is carried out in a biological safety cabinet, using a method of dropping bacterial liquid on a disc for culture testing.
[0051] Before the experiment, a solid culture medium was prepared. The culture solution was sterilized at high temperature and high pressure, concentrated to 20 μL, poured into a 10 mL container, and then 6 mL of sterile water was added to ensure that it was completely dissolved. Then 200 μL of E. coli culture solution was taken out from the test tube and placed in a centrifuge tube. 8 mL of PBS buffer was added as a blank control group. After stirring evenly, 30 μL was taken out and spread on the solid culture medium; 3 empty culture dishes were taken out and PLA discs of the same size were placed in each of them. 200 μL of bacterial solution was dropped on each disc, and they were placed in a 37 ℃ oven and cultured for 0h-6h (time interval was 0.5h). Then three example discs of the same size were taken out and cultured in the same way. After the culture was completed, it was placed in an empty centrifuge tube, 8 mL of PBS buffer was added, and ultrasonic treatment was performed for 5 minutes, and then 30 μL was taken out and coated on the surface. All the solid culture media after coating were marked with a marker and placed in a 37 ℃ oven for culture for 18 to 24 h, and then counted. The results are shown in the table. Figure 6 and Figure 7 The antibacterial efficiency calculation formula is as follows: R = (BC) / B×100% (1) In formula (1), R represents the antibacterial rate (%); B represents the colony count in the blank control group (CFU / mL); and C represents the colony count on the solid culture medium after 18 to 24 hours of culture (CFU / mL).
[0052] Depend on Figure 6 and Figure 7 It can be seen that the antibacterial effect of Example 4 is significantly improved compared with that of Comparative Example 1. The antibacterial rate of Example 4 is as high as 97% after 4 hours of culture, which is about 36% higher than that of Comparative Example 1; and the antibacterial rate of Example 4 is as high as 99.48% at 6 hours. It can be seen that the nanocellulose-chitosan bio-based antibacterial agent has a significant antibacterial effect on non-woven materials.
[0053] 5. Processing performance test of nonwoven materials The rheological properties of nonwoven materials were studied using a rotational rheometer. The oscillatory shear test was set in the range of 0.01-100 Hz at 190 °C and a strain of 1% was applied. The results are shown in Figure 2. Figure 8 shown.
[0054] from Figure 8It can be clearly seen from (a) and (b) that when the frequency increases, the storage modulus and loss modulus of the composite material have obvious changes, and the composite material shows a typical linear rheological phenomenon. At lower frequencies, the composite material is fully disentangled, so the storage modulus and loss modulus are low. When the frequency gradually increases, the chain segments have no time to relax and gradually show more obvious elastic behavior, so the storage modulus and loss modulus gradually increase. Comparing the two figures, the value of the loss modulus is greater than the storage modulus at the same frequency, which proves that the viscosity of the composite material is greater than the elasticity. With the addition of nanocellulose-chitosan bio-based antibacterial agent, the storage modulus and loss modulus show a gradual downward trend in the entire system. The reason is that the introduction of nanocellulose-chitosan bio-based antibacterial agent greatly reduces the interaction between molecular chains in the composite material, thereby improving its strength and elasticity, allowing the molecular chains of the polymer to move more easily, so the values of the storage modulus and loss modulus gradually decrease at the same frequency.
[0055] Depend on Figure 8 (c) It can be seen that as the frequency increases, the composite viscosity of the material gradually decreases. This is because in the process of gradually increasing shear rate, the molecular chain segments inside the material are oriented due to the action of external forces, resulting in relative movement, which causes the composite viscosity to decrease and shear thinning to occur; and at the same frequency, the composite viscosity of Examples 1-5 tends to decrease compared with that of Comparative Example 1, which indicates that the material has good fluidity, is conducive to processing and molding during the production process, and saves costs.
[0056] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a nanocellulose-chitosan bio-based antibacterial agent, characterized in that: The steps include: (1) Preparation of quaternized chitosan: first disperse chitosan in isopropanol and stir at 65-90°C for 1-2 hours to obtain a chitosan solution; then add an aqueous solution of 2,3-epoxypropyltrimethylammonium chloride and stir at the reaction temperature for 10-16 hours; after the reaction, filter and clean the obtained precipitate with isopropanol and ethanol in turn, dry and crush to obtain quaternized chitosan; (2) Preparation of oxidized nanocellulose: Dissolve the selective oxidant in water, add nanocellulose and mix to obtain a selective oxidant / nanocellulose mixed solution, place in a dark place, stir for 1-3 hours to form a gel solution, and then dilute with water and filter to obtain oxidized nanocellulose; (3) Preparation of nanocellulose-chitosan bio-based antimicrobial agent: dissolve the quaternized chitosan obtained in step (1) in 1-3% by volume acetic acid solution, and stir for 2-4 hours to obtain a homogeneous mixed solution containing quaternized chitosan; then add the oxidized nanocellulose obtained in step (2) to the homogeneous mixed solution, stir at a constant temperature of 40-79° C. for 1-3 hours, remove the acetic acid by rotary evaporation, dry and grind to obtain the nanocellulose-chitosan bio-based antimicrobial agent.
2. The method for preparing the nanocellulose-chitosan bio-based antibacterial agent according to claim 1, characterized in that: In step (1), the concentration of chitosan in the chitosan solution is 0.01-0.05 g / mL; the concentration of 2,3-epoxypropyltrimethylammonium chloride in the aqueous solution of 2,3-epoxypropyltrimethylammonium chloride is 0.1-0.3 g / mL; and the mass ratio of chitosan to 2,3-epoxypropyltrimethylammonium chloride is 1:3-10.
3. The method for preparing the nanocellulose-chitosan bio-based antibacterial agent according to claim 1, characterized in that: In step (2), the selective oxidant is sodium periodate, or a mixture of 2,2,6,6-tetramethylpiperidinyl oxide, sodium bromide and sodium hypochlorite in a mass ratio of 0.1-0.2:1-2:20-30.
4. The method for preparing the nanocellulose-chitosan bio-based antibacterial agent according to claim 1, characterized in that: In step (2), in the selective oxidant / nanocellulose mixed solution, the concentration of the selective oxidant is 0.02-0.04 g / mL, and the mass ratio of the selective oxidant to the nanocellulose is 2-4:
1.
5. The method for preparing the nanocellulose-chitosan bio-based antibacterial agent according to claim 1, characterized in that: In step (2), the nanocellulose is at least one of cellulose nanofibers, cellulose nanowhiskers, cellulose nanocrystals and bacterial nanocellulose.
6. The method for preparing the nanocellulose-chitosan bio-based antibacterial agent according to claim 1, characterized in that: In step (3), the ratio of the quaternized chitosan, acetic acid solution and oxidized nanocellulose is 1 g:70-100 mL:1 g.
7. Nanocellulose-chitosan bio-based antibacterial agent, characterized in that: Prepared according to the preparation method described in any one of claims 1 to 6.
8. A method for preparing a biodegradable nonwoven material, characterized in that: The nanocellulose-chitosan bio-based antibacterial agent described in claim 7 is uniformly mixed with polylactic acid, tough biodegradable material, epoxy chain extender, lubricant and antioxidant in a mixer, and then extruded, granulated and dried by a twin-screw extruder, and then melt-blown in a melt-blown device to obtain a biodegradable nonwoven material.
9. The method for preparing the biodegradable nonwoven material according to claim 8, characterized in that: The tough biodegradable material is at least one of poly(butylene terephthalate-adipate) (PBAT), poly(butylene succinate) (PBS), poly(butylene succinate-adipate) (PBSA) and poly(butylene terephthalate-succinate) (PBST); the lubricant is at least one of calcium stearate, magnesium stearate, zinc stearate, aluminum stearate, barium stearate and sodium stearate; and the antioxidant is at least one of hindered phenol antioxidants, hindered amine antioxidants, phosphite antioxidants and thioester antioxidants.
10. The method for preparing the biodegradable nonwoven material according to claim 8, characterized in that: The weight ratio of the nanocellulose-chitosan bio-based antibacterial agent, polylactic acid, tough biodegradable material, epoxy chain extender, lubricant and antioxidant is 0.5-5:40-60:40-80:0.5-2:0.1-1:0.1-1.
Citation Information
Patent Citations
A preparation method and application of polylactic acid melt-blown material
CN114957940B
An antibacterial absorbent nonwoven material for hygiene products
CN115624646B
Chitosan quaternary ammonium salt antibacterial cellulose and preparation method thereof
CN106905438A
Preparation method and application of antibacterial nano-fiber
CN110791829A
Heat-resistant antibacterial PLA (polylactic acid) full-biodegradable straw and preparation method thereof
CN114806113A